Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Unit Delivery Service PT PAM Lyonnaise Jaya Cabang Kebon Jeruk, Jakarta Barat Periode Juli – Desember Tahun 2022 - Damanik, Krisman; Sidjabat, Sonya (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study examines the impact of service quality and level of consumer satisfaction on customer loyalty at PT PAM Lyonnaise Jaya, which operates as a clean water provider for West Jakarta. The researcher applied a descriptive methodology with multiple regression analysis techniques, where the main data collection was carried out by distributing questionnaires to 60 respondents. The results of the analysis revealed that there was a positive influence of the service quality variable on consumer loyalty with a value of 0.126, while the customer satisfaction variable showed a more significant impact with a value of 0.167. When these two variables were tested simultaneously, it was found that they contributed 64.4% to the formation of customer loyalty, while the other 36% was influenced by variables outside the research. Based on these findings, it can be concluded that improving aspects of service quality and customer satisfaction has a real impact in building consumer loyalty. Thus, it is recommended that company management pay special attention to the development of these two aspects as a strategy to maintain and increase customer loyalty